Supervisor–Worker Relationship Dynamics for Workplace Violence Prevention in Public Sector Human Service Organizations. Issue 2 (15th March 2021) - Shier, Micheal L.; Turpin, Aaron; Nicholas, David; Graham, John R.
ABSTRACT: Supervisors of human service organizations can support violence prevention or contribute to experiences of workplace violence. This qualitative study sought to explore the ways in which supervisors prevent opportunities for workplace violence through their relationships with workers. Interviews with 81 workers in publicly administered human services in a Canadian province were analyzed using qualitative techniques. Results show that supervisor attentiveness, supervisor support, involvement by one's supervisor, and treating workers equally all contributed to workplace violence prevention. Findings provide important practical considerations that detail how supervisors play a critical role in supporting health and safety in human service workplace environments.